1967
DOI: 10.1111/j.1365-2621.1967.tb01952.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lipid Composition of Chicken Muscle During Frozen Storage

Abstract: SUMMARY —Fresh chicken muscle contained about 1.1% lipids, of which more than half was made up of phospholipids. Lipids from fresh muscle also contained about 30% triglycerides and small amounts of cholesterol, cholesterol esters, and free fatty acids. During storage at — 10°C, the phospholipid content of the muscle decreased and the free fatty acid and triglyceride contents increased. The decrease in phospholipid content resulted from loss of lecithins and cephalins. The sphingo‐myelin content remained the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

1968
1968
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 18 publications
2
9
0
1
Order By: Relevance
“…The data given in Table 1 also show that the phospholipid and triglyceride contents of the tissues studied decreased during frozen storage, but the monoglyceride, cholesterol, diglyceride, free fatty acid and hydrocarbon contents increased. These results c!osely agree with those reported by Davidkova and Khan (1967) ;Youssef et al (1983), Pikul et al (1985a, 1985b and Youssef and Rashwan (1989).…”
Section: Resultssupporting
confidence: 95%
“…The data given in Table 1 also show that the phospholipid and triglyceride contents of the tissues studied decreased during frozen storage, but the monoglyceride, cholesterol, diglyceride, free fatty acid and hydrocarbon contents increased. These results c!osely agree with those reported by Davidkova and Khan (1967) ;Youssef et al (1983), Pikul et al (1985a, 1985b and Youssef and Rashwan (1989).…”
Section: Resultssupporting
confidence: 95%
“…Cardiolipin was found in all tissues and was separated into two components which had chromatographic properties similar to phosphatidyl glycerol and polyglycerophosphate which were identified in chicken liver by Sgoutas (1966). As in a previous study (Davidkova and Khan, 1967), the levels of lysolecithin were found to be low in all tissues. Phosphatidyl inositol was also noted to be present in only small quantities, agreeing with data taken on chicken muscle (Peng and Dugan, 1965;Davidkova and Khan, 1967), but in disagreement with results of studies on liver (Sgoutas, 1966).…”
Section: Discussionmentioning
confidence: 69%
“…When tissue phospholipids were further separated, the phosphatides of choline, ethanolamine and serine, and sphingomyelin were identified (Peng and Dugan, 1965). More recently, traces of lysolecithin and phosphatidyl inositol have been reported in chicken muscle (Davidkova and Khan, 1967) and in chicken liver (Sgoutas, 1966). The latter study also revealed the presence of phosphatidyl glycerol and polyglycerophosphate in a "cardiolipin" fraction of chicken liver.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We cannot exclude the possibility of a complex being formed between unsaturated fatty acids and muscle proteins, as found by ANDERSON et al IS]. We could explain the faster reduction of unsaturated fatty acids in leg muscle, on the one hand, by the more intensive lipolytic processes in that type of meat [7], and on the other, by the catalytic action of heme pigments [12]. It is obvious from the results shown in the two tables, that the most intensive changes in the relative shares of fatty acids occurred in group IV in both types of meat.…”
Section: Resultsmentioning
confidence: 78%